Analysis of Mount Ruapehu tephra deposits from 4.3 to 6.1 ka : within a transitional timeframe : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Earth Science at Massey University, New Zealand - Fleming, Joseph (Massey University, 2024)
Mount Ruapehu is the largest active volcano in New Zealand, having shown a dominant eruptive record within the last 1,800 years. However, it showed a long period of relative dormancy beyond that time frame, extending to ~12 ka. Within this period of time sits the Papakai Formation. This formation is dominated by tephra deposits from the upper reaches of the Tongariro Volcanic Centre with only eight Ruapehu sourced tephras being found within the extents of this formation dating between 11-3.5 ka. This study aimed to analyse tephra deposits from Mount Ruapehu’s eastern ring plain found within the Papakai Formation. To define their geographical extents and physical characteristics within the field as well as their componentry and geochemical composition within the laboratory. Conducting this study allowed for insight into the eruptive processes from Mount Ruapehu throughout a period of dormancy as well as any trends in ashfall deposition and geochemistry over time. Two black ash layers found beneath the Taupō Ignimbrite were sampled and collected alongside the five Papakai Formation tephras for comparison. Four of the five layers had been previously identified by Donoghue (1991) but had not been fully analysed with field observations having only been made at a handful of locations. This study aimed to provide more information of the ashfall deposits. The two black ash layers and three orange lapilli layers within the Papakai Formation were found to be basaltic andesite with each showing definable traits and characteristics within the field. The tephras showed a trend towards higher silica content over time with deposits younger than the Taupō Ignimbrite being dacitic in nature (Voloschina, 2020). This trend could reflect the lower eruptive frequency of Mount Ruapehu within the span of the Papakai Formation and could potentially show the point at which volcanic activity reactivated at the southern crater after a long period of dormancy. Maximum extents to the north, west and south were estimated but access into the Rangipo Desert would be required to provide a more accurate analysis on the geographical extents of each tephra layer within the eastern ring plain stratigraphy.
Keywords: 370512 Volcanology